Electrochemical Advanced Oxidation of Carbofuran in Aqueous Sulfate And/Or Chloride Media Using a Flow Cell with a Ruo2-Based Anode and an Air-Diffusion Cathode at Pre-Pilot Scale - Salazar-Gonzalez, R (Elsevier B.V., 2018)
The treatment of 0.348 mM carbofuran solutions in 0.050 M Na2SO4 at pH 3.0 has been studied by electrochemical oxidation with electrogenerated H2O2 (EO-H2O2), electro-Fenton (EF) and photoelectro-Fenton (PEF). The trials were performed in a 2.5 L pre-pilot plant equipped with a filter-press cell, which contained a RuO2-based anode and an air-diffusion cathode, connected to an annular photoreactor with a 160 W UVA lamp in PEF. The oxidizing species were the [rad]OH generated at the anode from water oxidation and in the bulk from Fenton s reaction between added Fe2+ and H2O2 produced at the cathode. The oxidation power of treatments rose in the order EO-H2O2 ≪ EF < PEF, demonstrating the preponderant role of [rad]OH in the bulk. The drug decay always obeyed a pseudo-first order kinetics. Similar TOC abatements of 82%–88% were found in PEF operating at different current densities and carbofuran concentrations, ascribed to the additional photolytic action of UVA light to remove photoactive intermediates, also allowing a gradual detoxification. In matrices with Cl−, active chlorine was also produced as oxidant and its quick reaction with carbofuran caused its faster decay at increasing Cl− content. However, lower mineralization was achieved because of the accumulation of recalcitrant chloroderivatives. GC–MS analysis of treated solutions with 0.070 M NaCl corroborated the formation of 6 chloroderivatives, whereas 5 heteroaromatics were detected in 0.050 M Na2SO4. Oxalic acid was accumulated in the latter medium since its Fe(III) complexes were stable in EF and rapidly mineralized by UVA light in PEF. The mineralization of urban wastewater spiked with carbofuran by PEF in the pre-pilot plant was partial due to the recalcitrant chloroderivatives formed from carbofuran and natural organic matter. © 2017 Elsevier B.V.